Research On the Sustainability of Snow Tires Casing for Retreading Purpose in Malaysia: An Exploratory Study - Mad Lazim, Halim; Osman, Wan Nadzri; Mohtar, Shahimi; Taib, Che Azlan; Iteng, Rosman; Abdul Rahim, Mohd Kamarul Irwan; Ariffin, Ahmad Shabudin; Othman, Nora'en; Chan, Boon Liat; Hashim, Mohd Zahrin
Retreading a tire is a re-manufacturing process through which old and worn out tire treads are replaced by new ones. The global retread tires market is estimated to have been valued at US$ 8,684.9 million at the end of 2017 and is expected to reach US$ 13,647.2 million by the end of 2028 while expanding at a compound annual growth rate of 4.6% over the forecast period. The immersive retread tires industry has been growing in Malaysia for a long time and more than 60 local tire manufacturers are registered with MS 224 certification with over two million was produced each year. Retread tires was safe to use on the road as it was tested using the same performance test as the new tire. For the purpose of seeing the durability of the truck tire casing used, a laboratory test was conducted. The results of this test found that the retread tires passed the MS 224 performance test, and also complied with the MS224 marking test in addition to the marking test for the used case. The report concludes that retreaded tires show no greater likelihood of failure in service than a first life tire when considering these results against the market usage of new tires vs retreaded tires.